THE EFFECT OF DIFFERENT FEED PROCESSING TO DECREASED LEVELS OF HCN ON CASSAVA LEAVES FOR RUMINANT FEEDS - Wenda, Kalinus (Universitas Kanjuruhan Malang, 2014)
This study was aims to determine the effect of different feed processing to decreased levels HCN content of cassava leaves for feeding ruminants. This research was conducted in the Laboratory of the Animal Husbandry Faculty of integrated farm Kanjuruhan University Malang on 1 to 15 November 2013. The materials used cassava leaves and cassavas. Methods used completely randomized (RAL). Each treatment was repeated 3 times, if there was different in test followed by least significant different (LSD). The variables measured were decreased levels of HCN of cassava leaves.The results showed that the effect of feed proccesing highly significant to decrease in HCN content (p<0,01). The decreased in HCN content to the highest in treatment p3 is 33.34%.Based on the results on the study concluded that the treatment cassava leaves gave best results indecreased of HCN content. So it is advisable to introduce the fermentation of cassava leaves to improve the quality of animal feed.Keyword : HCN, feed processing, cassava, ruminant feed